2016
DOI: 10.1021/acscatal.5b02593
|View full text |Cite
|
Sign up to set email alerts
|

Trace Amount of SnO2-Decorated ZnSn(OH)6 as Highly Efficient Photocatalyst for Decomposition of Gaseous Benzene: Synthesis, Photocatalytic Activity, and the Unrevealed Synergistic Effect between ZnSn(OH)6 and SnO2

Abstract: It is still a challenge to develop a high performance photocatalyst for the abatement of aromatic compounds like benzene (C6H6) that has been regarded as a priority hazardous VOC substance in the indoor atmosphere. Zinc hydroxystannate (ZnSn(OH)6, ZHS) is a promising material for the application. However, the key structural features which responsible for the high activity are still ambiguous. To address this issue, a series of ZHS with different surface properties was hydrothermally synthesized by varying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 100 publications
2
26
0
Order By: Relevance
“…Although ZTO shows the highest efficiency for C6H6 conversion, the mineralization of C6H6 is only 60.4%. Consistent with the reported works [42,60], P25 shows low activity for the degradation of gaseous C6H6 and the C% of C6H6 is only 9.6%.…”
Section: Photocatalytic Activitysupporting
confidence: 90%
See 2 more Smart Citations
“…Although ZTO shows the highest efficiency for C6H6 conversion, the mineralization of C6H6 is only 60.4%. Consistent with the reported works [42,60], P25 shows low activity for the degradation of gaseous C6H6 and the C% of C6H6 is only 9.6%.…”
Section: Photocatalytic Activitysupporting
confidence: 90%
“…As shown in Fig. 7 The mineralization of C6H6 on P25 is not as significant as the decoloration of MO and a color change of P25 from white to slight brown has been observed suggesting the deposition of intermediates [42,60]. ZTO shows the highest mineralization rate of C6H6 and the average rate is 62.1 μmol·h −1 ·g −1 .…”
Section: <Fig 7>mentioning
confidence: 90%
See 1 more Smart Citation
“…[7][8][9] To solve the problem, exploitation of new photocatalysts with excellent activity is one of the developing directions of photocatalysis. [10][11][12] In numerous photocatalysts, BiPO 4 has drawn much great attention in recent years. [13][14][15][16][17][18][19][20][21][22][23][24] For example, Zhu's group 13 reported that the photocatalytic activity of BiPO 4 is superior to P25 (TiO 2 , Degussa) under UV light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 , ZnO, SnO 2 , etc.) for photocatalytic applications, zinc oxide (ZnO) has grown considerably, due to its physical and chemical stability, high catalytic activity, low cost, environmental friendliness and easy of availability . However, enhancing the photocatalytic efficiency of ZnO to meet the practical application requirements is still a challenge because of the bottleneck of poor quantum yield caused by the rapid recombination of photogenerated electrons and holes .…”
Section: Introductionmentioning
confidence: 99%